The Impact of Internet Addiction on Children’s Self-Control - Salsa Lutfiah Zahra; Miratul Hayati (UPI Kampus Cibiru, 2022)
Internet playing activities for early childhood without supervision will lead to a condition of internet addiction. Internet addiction affects children's self-control. Self-control is the main thing for children to live their lives in the future. If the child has low self-control, then he will have difficulty in deciding and solving a problem well. The purpose of this study was to examine the impact of internet addiction on children's self-control. This research uses descriptive qualitative method. Data collection through interviews and observations and data analysis using Miles Huberman analysis, which comprises several stages, namely data collection, data reduction, data presentation and data verification. This study describes the impact of internet addiction on aspects of self-control in children aged 5-6 years including (1) types of internet users in children (2) user aspects (3) factors causing internet addiction in children (4) the impact of internet addiction on children's self-control in behavior-control, cognitive-control and decisional-control.